Elevated CD8+ IL-17+ Tc17 Levels and Their Correlation with Disease Activity in Patients with Rheumatoid Arthritis - Ning LI,; Jie HAN,; Jie-Ru ZHOU,; Jia-Yi WANG,; Jie ZHANG,; Song-Guo ZHENG2, (Archives of Rheumatology, 2013)
Objectives: In this study, we aimed to determine the role of CD8+IL-17+ double-positive T cells (Tc17) in the pathogenesis and activity of rheumatoid arthritis (RA). Patients and methods: The frequency and distribution of the Tc17 cells were identified using double immunofluorescent staining in peripheral blood mononuclear cells (PBMCs), synovial fluid mononuclear cells (SFMCs), and synovial tissues in RA patients. Soluble interleukin (IL)-17 levels were measured using the enzyme-linked immunosorbent assay (ELISA). Real-time polymerase chain reaction (PCR) was used to determine the IL-17 messenger ribonucleic acid (mRNA) in CD8+ T cells. The correlation between the Tc17 cells and RA clinical parameters, including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), rheumatoid factor (RF), and Disease Activity Score 28 (DAS 28), a test used for the evaluation of the 28 commonly affected joints in RA, was analyzed. Results: The frequency of Tc17 in the PBMCs of the RA patients was higher compared to the healthy controls. The frequency of Tc17 cells in the SFMCs of the RA patients was also higher than that found in the RA PBMCs and OA SFMCs. The IL-17 mRNA expression in the RA CD8+ T cells was significantly higher than in the healthy controls. The levels of soluble IL-17 in the sera and synovial fluid of the RA patients were significantly higher than those of the healthy control and OA groups. There was a significant positive correlation between the frequency of Tc17 cells in the SFMCs and DAS 28 scores in the RA patients. Conclusion: Our study results strongly demonstrated that a new Tc17 subset existed in RA patients and its frequency was significantly correlated with the disease activity of RA patients. Thus, our study suggests that Tc17 cells along with other IL-17- producing cells, may play an important role in the pathogenesis of RA.